The concept of ‘impartition’ policies: A different approach to vertical integration strategies - Barreyre, Pierre-Yves (Strategic Management Journal, 1988)
Abstract The inverse of vertical integration, ‘impartition’, is defined as an entrepreneurial behaviour which consists in casting other firms (partners) for different parts of its overall system of activities. A firm imparts when, in order to allocate its own resources to activities more congruent with its strategic objectives, it contracts out instead of doing in‐house. This concept also involves a cooperative attitude towards partners for a mutual profit based on external synergies. The developed pattern has a large range of applications: subcontracting, proxy agreements, agency contracts, international production sharing, product mandating, franchising, licensing and a growing number of intangibles. The use of the impartition leverage may amplify the strategic power of a firm and its capacity for fast growth. In response to severe worldwide competition and accelerating technological and social changes, four overall principles underlie an impartition policy: high turnover, organizational flexibility, strategic mobility and external synergies. In conclusion the author insists on the necessity of mastering the art of resources management.